The Chemical Composition of Gracilaria verrucosa Extract and its Utilization on Survival and Growth Litopenaeus vannamei - Jasmanindar, Yudiana; Sukenda, Sukenda; Alimuddin, Alimuddin; Junior, Muhammad Zairin; Utomo, Nur Bambang Priyo (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
The Gracilaria genus is a potential source of natural and environmentally-friendly alternatives in improving the survival and growth of shrimp. This study aims to identification immunostimulant molecules extract G. verrucosa and evaluate the utilization of G verrucosa extract as an immunostimulant in improving survival and growth of L. vannamei. Seaweed extraction used ethyl acetate then formulated in the diets. The immunostimulant molecule in the G. verrucosa was analysis. The shrimp were fed a test diet containing extract G. verrucosa at a dose of 2 g kg-1 or extract G. verrucosa-free control diets for 42 days. Shrimps were fed diets containing extract with a specific duration. The observation on the survival and growth of L. vannamei was performed after maintenance at the Laboratory for six weeks. Following, diets containing extract was tested in the field (pond shrimp farm) at the same dose of extract for 58 days. Shrimp was feed diets containing extract once a week, once in the early culture, and diet control, then the survival and growth shrimp were analysis. Concentrations of sulfates and carbohydrates in G. verrucosa ethyl acetate-extract were 24.21% and 13.41%, and crude protein 3.64%. GC-MS pyrolysis results show that G. verrucosa polysaccharide is similar to immunostimulant molecules. The survival shrimp gave diets containing G. verrucosa extract formulation was higher than that of shrimps fed controls diet. The Shrimp fed diets extracts have higher growth than shrimp given control dietsKeywords: Gracilaria, extract, polysaccharides, immunostimulant